The Fairwork Project: Promoting Good Labor Practices in the Digital Platform Economy through Action Research - Tatiana López; Funda Ustek-Spilda; Patrick Feuerstein; Fabian Ferrari; Mark Graham (Collaborative Research in the Datafied Society: Methods and Practices for Investigation and Intervention, 2024)
Though the digital platform economy in some contexts has created new employment opportunities, work in the platform economy has been widely criticized for its often precarious and exploitative character. One central mechanism through which digital platforms construct and conceal exploitative employment relations are information asymmetries among platforms, workers, and consumers. These information asymmetries are created through, among other things, a lack of transparency on how platforms allocate work, calculate payments, and use customer reviews for incentive structures and other rating-based work outcomes. Against this backdrop, the Fairwork project conducts action research to tackle these information asymmetries. In this chapter we introduce the Fairwork project and provide critical insights into our engagement with platforms as an action research strategy.
Keywords: 330; Gig economy; Exploitation; Social transformation; Independence